ISSUES OF EVALUATING THE EFFICIENCY OF THE INVESTMENT ENVIRONMENT IN THE REGIONAL ECONOMY - Abdiyeva Nargiza,; Begasilova Dilnora, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses theoretical and practical aspects of evaluating the efficiency of the investment environment in the regional economy. Scientific approaches to the concept of the investment environment have been studied. Proposals are presented for assessing investment activity and the effectiveness of the investment environment in the region.